Effect of Cover Crops, and the Management Thereof, on the Weed Spectrum in a Drip-irrigated Vineyard: 1. Weeds Growing During Winter and From Grapevine Bud Break to Grapevine Berry Set - Fourie, J.C.; Kunjeku, E.C.; Booyse, M.; Kutama, T.G.; Sassman, L.W. (South African Journal of Enology and Viticulture, 2017)
A five-year trial (2009 to 2013) was executed in a drip-irrigated full-bearing seven-year-old Shiraz/101-14 Mgt vineyard established on a sandy to sandy clay loam soil at Blaauwklippen Farm (33°58’S, 18°50’E) near Stellenbosch, South Africa. Fourteen treatments, consisting of two management practices applied to five cover crop species, as well as winter-growing weeds (no cover crop) and winter-growing weeds (no cover crop) with nematicide applied in the vine row, were applied. The effect of the five cover crop species, either controlled chemically (CC) or mechanically (MC) during grapevine bud break, on the weed spectrum was determined at the end of winter and during grapevine berry set. Total suppression of Lolium species (ryegrass) was achieved with Avena sativa cv. Pallinup (oats) (CC) and Eruca sativa cv. Nemat (Nemat) (CC) after three years. A grass-specific herbicide applied at the end of May 2012 terminated the dominance of ryegrass and facilitated the dominance of Erodium moschatum (musk heron’s bill). Sowing the cover crops as late as 2013-05-23 prevented ryegrass from regaining its dominance. After five winters, ryegrass was totally eradicated from oats (CC), oats (MC), Sinapus alba cv. Braco (white mustard) (CC) and Nemat (CC). Musk heron’s bill was totally suppressed in all treatments during berry set within two seasons and ryegrass in all the CC treatments by 2011. This probably facilitated the dominance of Digitaria sanguinalis (crab fingergrass).